Cape verde : Third Review Under the Three-year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver and Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2003)
The performance criteria have not been met, but Executive Directors commend the government for taking corrective actions and for their commitment to maintain the pace of structural reforms. The government is urged to prepare a quality poverty reduction strategy paper as quickly as possible. Progress has been made in preparing to implement the value-added tax and the new customs tariffs. The government's strong track record of pursuing prudent fiscal and monetary policies while redirecting public expenditures toward key social services is commended.